2011
DOI: 10.1007/jhep06(2011)022
|View full text |Cite
|
Sign up to set email alerts
|

Large-θ 13 perturbation theory of neutrino oscillation for long-baseline experiments

Abstract: The Cervera et al. formula, the best known approximate formula of neutrino oscillation probability for long-baseline experiments, can be regarded as a second-order perturbative formula with small expansion parameter ǫ ≡ ∆m 2 21 /∆m 2 31 ≃ 0.03 under the assumption s 13 ≃ ǫ. If θ 13 is large, as suggested by a candidate ν e event at T2K as well as the recent global analyses, higher order corrections of s 13 to the formula would be needed for better accuracy. We compute the corrections systematically by formulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 81 publications
5
91
1
3
Order By: Relevance
“…Taking ee , eµ and eτ equal to zero, the disappearance probability can be written as Our result agrees with ref. [43] for the SM terms (in the first two lines) and with ref. [42] for the NSI terms up to second order after making the assumption that terms of order cos 2θ 23 2 can be ignored.…”
Section: Oscillation Probabilitiesmentioning
confidence: 95%
“…Taking ee , eµ and eτ equal to zero, the disappearance probability can be written as Our result agrees with ref. [43] for the SM terms (in the first two lines) and with ref. [42] for the NSI terms up to second order after making the assumption that terms of order cos 2θ 23 2 can be ignored.…”
Section: Oscillation Probabilitiesmentioning
confidence: 95%
“…Therefore, v can be treated as a small parameter of order . At the first oscillation maximum, the ν µ → ν e conversion probability in matter can be obtained (see the appendix in [19] and the works [47][48][49]) by performing, in the leading term of the vacuum probability, the following substitution 10) which incorporates the (third order) corrections due to matter effects. It can be shown that the two interference terms acquire corrections which are of the fourth order.…”
Section: Analytical Expressions In Vacuum and Mattermentioning
confidence: 99%
“…This is important considering that simulation of LBL experiments and performing χ 2 -fits require a fast and simple method to compute a large number of oscillation probabilities. Therefore even though the numerical calculation is always viable, there are still many studies on analytic approximation formulae for neutrino oscillation in matter [13,[30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Jhep10(2015)090mentioning
confidence: 99%